THE EFFECT OF ABC RUNNING TRAINING TO INCREASING ACCELERATION IN UNPATTI SPRINT ATHLETES - Rumareate, Maikel; Syaranamual, Jusak; Tahapary, Johni Melvin (JARGARIA SPRINT: Journal Science of Sport and Health, 2023)
This study aims to determine how much influence running abc exercise has on increasing acceleration in SSC unpatti sprint atlethes. This research is an experimental research, where the writer wants to know the effect of running abc training on increasing acceleration in SSC unpatti sprint athletes. The method used in this research is a field experiment methoad. The population used as the sample in this study amounted to 20 people, so this research was a population study. The variables in this study are the independent variable and the dependent variable, the independent variable is the running abc exercise and the dependent variable is the 30 meter acceleration test. The instrument used in the training process consists of nine forms of training. Based on the results of the pre-test and pro-test wich were processed using statistical formulas, the hypotheses in the study can be provend that there is an increase in acceleration in SSC unpatti sprint athletes through running abc exercises